A review and assessment of currently available data of the EGFR antibodies in elderly patients with metastatic colorectal cancer. Issue 2 (March 2016) - Rosati, Gerardo; Aprile, Giuseppe; Cardellino, Giovanni Gerardo; Avallone, Antonio
Abstract: Although the number of elderly patients is increasing each year, this population has been under-represented in clinical trials. At the same time, the survival of patients with metastatic colorectal cancer has been improving, not only because of improvements in chemotherapy, but especially because of the addition of monoclonal antibodies (bevacizumab, cetuximab and panitumumab). Therefore, it is necessary to define the role of these new drugs in the elderly population, a group that is heterogeneous and consists of those who are fit and able to tolerate all therapies equally as well as younger patients and unfit individuals who should only given best supportive care or therapies specifically modulated for them. Today, although data from phase II–III studies have helped to establish the role of bevacizumab in the elderly, few trials have studied anti-epidermal growth factor receptor (EGFR) antibodies in the same population. This review presents the results of studies carried out with anti-EGFR agents, with a hope that more trials will be carried out with these drugs in the elderly in the future.